Economic and zoological rationale for using new bedding material for lactating cows - Danilova Nadezhda; Kuznetsova Elena; Beloglazova Olga (BIO Web of Conferences, 2022)
This article examines the influence of the studied bedding material, which is dust-free wood shavings, cleaned from metal impurities and processed by thermochemical and biotechnological methods on the productivity of cows, the sanitary and hygienic quality of milk and the profitability of the products obtained. The production experience was carried out in the conditions of one of the farms of the Republic of Tatarstan on cows of the Holstein-Friesian breed and lasted for 3 months. To assess the quality of milk, the following indicators were taken into account: the amount of fat, protein, lactose, dry matter, non-fat milk solids, urea, somatic cells, as well as acidity, freezing point, pH, analysis for ketone bodies. The milk production was calculated based on the results of the control milking. Our studies have shown that, from an economic point of view, the use of the investigated bedding material is most effective.